Compression Ratio Effect on the Performance and Emission of CI Engine Fueled with Waste Cooking Oil Methyl Ester and Diesel Blends at Constant RPM - Tirkey J.V.; Shukla S.K.; Singh A.K. (My University, 2025)
Most of the rural areas lack electric power and the blended-fuel engines can be run for electric generation. In this experimental study, combustion, performance, and emission characteristics of a single-cylinder four strokes variable compression ratio engine fueled with waste cooking methyl ester at 10%, 20%, 30%, 40%, 50% blends with diesel oil and fuel economy have been compared to the conventional diesel. The used biodiesel was produced from waste cooking oil by transesterification. Experiments have been performed at a constant speed of 1500 rpm at full load by varying compression ratios from 15:1 to 18:1. The results about cylinder pressure, net heat release, exhaust gas temperature, brake thermal efficiency and exhaust emissions of NOx CO, CO2 were presented. They showed that the maximum cylinder pressure was higher for all the biodiesel blends and increased with the compression ratio while the net heat release decreased with the compression ratio increase. Exhaust gas temperature was found to be higher for diesel while the biodiesel B40 achieved the highest temperature. Brake thermal efficiency decreased for all the biodiesels compared to the usual diesel. B50 efficiency is 10.68% less than that of the diesel. The biodiesel addition also increased NOx emission up to 35.36% for B50 and CO emission decreased by 17.5%. on average. © 2021, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.